Predicting work engagement among young adult cancer survivors: a moderated mediation model - Musa, Siti Nur Syuhada; Hamzah, Siti Raba'ah; Muda, Zulaiha; Asimiran, Soaib; Krauss, Steven E. (Frontiers Media, 2023)
Introduction: Early research on cancer survivors was focused on exploring cancer treatments. More recently, attention has shifted to cancer survivorship research, focusing on cancer survivors as individual persons, including the multiple facets of survivors' quality of life but is inapplicable in the context of work-related role played in the young adult cancer survivors' lives. However, in recent studies on the outcomes of long-term survivorship, some of the main areas of cancer survivorship research revolves around employment issues of young adult cancer survivors. In the present study, the focus is given on the role of workplace spirituality as a mediator on the association of employee resilience and workplace social support on work engagement in a Malaysian setting, taking into consideration gender and age differences.